67 Reducing chest pain admissions using a 1 hour high-sensitivity troponin-t pathway. (5th June 2017) - Richards, Gavin; Sen, Gautam; Halliday, Alison; Thomas, Sadie; Stevenson, Emma; Gillings, Marianne; Scott, Peter
Abstract : Introduction: Chest pain is the most common presenting complaint to emergency departments in the United Kingdom. Existing management pathways for suspected Acute Coronary Syndrome utilise serial cardiac troponin measurement, typically at admission and again at 6 or 12 hours, often necessitating inpatient admission. Recent work has validated the use of a high sensitivity Troponin assay to enable risk stratification using presentation and 1 hour Troponin concentrations, with a view to reducing admissions and facilitating safe, early discharge. Methods: A 1 hour troponin pathway was implemented in a District General Hospital (DGH) at Gloucestershire Royal Hospital, using a High Sensitivity Troponin-T assay (hs-cTnT, Elecsys assay, Roche Diagnostics ®). This was trialled in the Emergency Department for 56 consecutive hours. Patients with suspected ACS had a plasma hs-cTnT concentration measured at presentation, and if necessary a repeat test was performed at 1 hour. Patients were then stratified using the 1 hour Troponin pathway into low, medium and high risk groups. All instances of hs-cTnT performed for 112 consecutive hours were included in analysis, 56 hours of the trial period and 56 hours of control data for comparison. We reviewed the cases to assess the performance and safety of the 1 hour troponin pathway using primary outcome data of discharge rates and subsequent myocardial infarction or death within 30 days. Results: 140 patients had a hs-cTnT performed. 51 cases did not present with chest pain or were admitted with a non-ACS diagnosis and were excluded from further analysis. During the trial period 21 (54%) of patients were discharged directly home from the Emergency Department, compared with 15 (30%) during the control period (p=0.02; n-1 two-proportion (Ã□â€¡ 2 ) analysis ). There were no documented cases of subsequent myocardial infarction or death within 30 days follow up. Conclusions: There was a substantial increase in the percentage of patients discharged home from the Emergency Department during the 1 hour Troponin trial compared with the control period, demonstrating that this pathway facilitates rapid decision making and early discharge. Our estimate is that a further 3 admissions could have been avoided during the trial period if the pathway had been strictly implemented, and we predict that further education and familiarity for the Emergency Department staff will improve this. There were no cases of acute myocardial infarction or death in our cohort at 30 days, meaning that patient safety does not appear to be comprised. To our knowledge this is the first trial of a 1 hour Troponin pathway in a UK DGH, and demonstrates that a 1 hour model can be applied to an unselected population and can safely reduce acute hospital admissions.